Nāṭār eṉṉuñ col ārāycci : araca kulattaik kuṟittu eḻutiya ōr pirapantam - Vijaya Turaicāmi Kirāmaṇi, Ta (SAMP early 20th-century Indian books project ;, 1927)
Etymological analysis of the word "Nāṭār"